Significance of Doshas in Management of various Disease - Asthana, Alok Kumar; Asthana Monika, Monika; Sahu, Renu (Asian Journal of Pharmaceutical Research and Development, 2018)
In Ayurveda, the span of life is described to be determined on the basis of nature of the physique, type of constitution. The utility of Ayurveda is to help maintain the health of a healthy individual and cure of disease of a patient. In our ancient text, the pathogenic factor in the body are Vayu, Pitta and Kapha, while those in the mind are Rajas and Tamas. Out of three. qualities (Gunas) of mind viz., Sattva, Rajas, Tamas, it is only the latter two that cause vitiation of the mind, the former one being non-pathogenic.In other words, Vayu, pitta and Kapha are, somatic Doshas and Rajas and Tamas are the psychic ones. These three Doshas when vitiated harmful to our Dhatu (tissue) and donate life in an unvitiated state, which means helping in the acquisition of health.so for the healthy life equilibrium of Doshas is mandatory. KEY WORDS: Vata, moksha, pitta, kapha, shleshma.